CLASSIFICATION OF STYLISTIC DEVICES.THE NATURE TYPES AND FUNCTIONC OF LEXICAL STYLISTIC DEVICES: METAPHOR, METONYMY (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The most essential feature of the word is that it expresses the concept of a word or a phenomena through its form and meanings. There are 3 types of lexical meanings: Logical meaning (dictionary); Nominative meaning; Emotive meaning.